A REVIEW OF RESILIENCE IN GLOBAL SUPPLY CHAINS: STRATEGIES, CHALLENGES, AND FUTURE DIRECTIONS - Shilpa Malge``; Akarshan Gulhane; Prof. Eshant G. Rajgure (International Engineering Journal For Research & Development, 2024)
The modern economy is based on global supply chains, which make it easier for information, goods, and services to travel across national boundaries and continents. But these supply chains have faced previously unheard-of difficulties recently, endangering their resilience and stability. The business environment is becoming more complex due to factors including fast technical improvements, changing consumer tastes, and changing regulatory environments. These factors have made supply chain operations more complex. In addition, new risks and uncertainties have entered the global trade scene due to geopolitical uncertainties like trade disputes and geopolitical tensions, upending long-standing supply chain networks and partnerships. Natural disasters, including earthquakes, hurricanes, and floods, have long been recognized as significant threats to supply chain continuity. The impact of these events can be far-reaching, disrupting production facilities, transportation networks, and distribution channels, leading to delays, shortages, and increased costs. Furthermore, the advent of worldwide pandemics, such the COVID-19 outbreak, has brought attention to the weaknesses present in international supply networks. The pandemic has generated significant disruption, including lockdowns, travel restrictions, and supply chain interruptions. This has highlighted the need for increased resilience and exposed the fragility of current supply chain architecture. Organisations are seeing more and more how critical resilience is to their supply chain strategies as a reaction to these issues. In supply chain management, resilience is the system's capacity to tolerate disturbances, adjust to shifting circumstances, and bounce back swiftly from setbacks. It includes a variety of preventative actions and tactics meant to enhance supply chain processes with redundancy, adaptability, and agility. This paper aims to provide a comprehensive review of resilience in global supply chains, examining various dimensions of resilience, including its conceptual framework, strategies for building resilience, challenges faced by organizations, and future research directions. Through an extensive literature review, this article synthesizes existing research findings and insights to offer a holistic understanding of resilience in global supply chains.